A Fingerprint &Pin Authentication to Enhance Security At The Automatic Teller Machines - Madara, Dondo Jacqueline Akinyi; Okeyo, George; Kimwele, Michael (International Journal of Scientific & Engineering Research, 2017)
The need of money can only be satisfied when you are carrying money with you. That also increases the risk of getting robbed. This researchfocuses on how to enhance security of transactions in Automatic Teller Machine system using a multi-factor authentication system (PIN and Fingerprint). This research proposeda highly secured Automatic Teller Machine banking system using an optimized Advanced Encryption Standard (AES) algorithm. This research proposes two levels of security. Firstly we consider the security level at the client side by providing biometric authentication scheme along with a password of 4-digit long. Biometric authentication is achieved by considering the fingerprint image of the client. Secondly we ensure a secured communication link between the client machines to the bank server using an optimized energy efficient AES processor. The fingerprint image is the data for encryption process and 4-digit long password is the symmetric key for the encryption process. To get a low power consuming Automatic Teller Machine, an optimized AES algorithm is proposed in this research. In this system biometric and cryptography techniques are used together for personal identity authentication to improve the security level.
Keywords: AES Algorithm; AES Processor; ATM; Biometric; Cryptography; Encryption; Fingerprints; Multi-factor